Gambaran Persepsi Siswa SMA Terhadap Pernikahan Dini Di SMA Negeri 1 Limboto - Mutmainnah Indah Safitri Otoluwa; Lintje Boekoesoe; Ika Wulansari (An Idea Health Journal, 2023)
Teenagers' perception of early marriage can be a basis for teenagers in making decisions to do or not to do early marriage. Information and knowledge of adolescents is an important factor in the formation of perceptions. Cognitive aspects, affective aspects, and conative aspects are aspects of perception that influence adolescents in perceiving something. This study aims to describe student perceptions of early marriage at SMA Negeri 1 Limboto. This research is a type of quantitative research using a descriptive design. The population in this study amounted to 320 people with a sample of 247 respondents using a total sampling technique and using inclusion and exclusion criteria. Based on the results of the study, it was found that, out of 247 respondents, the majority of respondents had positive perceptions, namely 187 respondents (75.7%). And 60 respondents (24.3%) have a negative perception. This research is expected to be input for schools to always care and play an active role in preventing sexual deviant behavior among teenagers so that high school students avoid promiscuity that leads to early marriage.